2020
DOI: 10.1136/oemed-2020-106540
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic growth and influencing factors among frontline nurses fighting against COVID-19

Abstract: ObjectiveTo explore the level and influencing factors of frontline nurses’ post-traumatic growth (PTG) during COVID-19 epidemic.MethodsA cross-sectional survey was conducted in February 2020 in three hospitals in China. The Post-traumatic Growth Inventory (PTGI) was used to investigate the PTG of frontline nurses. Data on related factors, including demographic characteristics and subjective variables, were collected. The Event-Related Rumination Inventory was used to assess rumination. Pearson’s or Spearman’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
168
4
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(198 citation statements)
references
References 27 publications
20
168
4
6
Order By: Relevance
“…We investigated the prevalence of anxiety and depression by risk groups and found higher levels of anxiety and depression (as expected) among frontline responders as compared to the second-line workers. All of these results may be partly confounded by the fact that majority of the frontline workers' group constitutes nurses, who are responsible for providing direct care to the COVID-19 patients and for collecting sputum specimen for virus detection, and tend to be female [3,27,28,[94][95][96][97]. This repeats a finding from the SARS outbreak that nurses reported higher anxiety, depression, behavioral problems, and moral injuries (related to death and ethical dilemmas) [3,5,7,14,27,28,[92][93][94][95].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated the prevalence of anxiety and depression by risk groups and found higher levels of anxiety and depression (as expected) among frontline responders as compared to the second-line workers. All of these results may be partly confounded by the fact that majority of the frontline workers' group constitutes nurses, who are responsible for providing direct care to the COVID-19 patients and for collecting sputum specimen for virus detection, and tend to be female [3,27,28,[94][95][96][97]. This repeats a finding from the SARS outbreak that nurses reported higher anxiety, depression, behavioral problems, and moral injuries (related to death and ethical dilemmas) [3,5,7,14,27,28,[92][93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence of the psychosocial impact of COVID-19 on health care workers found in this study draws more careful attention to educational and policy interventions for this subgroup. Educational and behavioral interventions emphasizing hardiness, social support, positive thinking, a sense of coherence, and others have been advocated in the literature [96][97][98]. The role of self-care is also highlighted by some researchers [98][99][100].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current narrative on psychological wellbeing of frontline healthcare workers (HCWs) during the coronavirus disease 2019 (COVID-19) pandemic has been highly polarized by a predominant focus on distress: most studies have painted a picture of a fragile group with mental health needs that need prioritizing (Dutheil, Mondillon, & Navel, 2020 ; García-Fernández et al, 2020 ; Holmes et al, 2020 ; Romero et al, 2020 ), while a few others depict HCWs as resilient and endowed with super-hero abilities (Cui et al, 2021 ; Stokes-Parish, Elliott, Rolls, & Massey, 2020 ).…”
Section: Dear Editormentioning
confidence: 99%
“…During the COVID-19 pandemic, Kristine Olson and Martin Huecker emphasized the great significance to study PTG and its facilitators among HCWs ( 11 , 12 ). A study conducted in February 2020 showed that 167 frontline nurses in Henan and Hubei, China, had demonstrated a moderate and above level of PTG during the early stages of the pandemic, meanwhile, the PTG level was associated with working years, self-confidence in frontline work, awareness of risk, psychological intervention, or training and deliberate rumination ( 13 ). Another large-scale survey conducted in April 2020 discussed relationship among burnout and PTG, influencing factors of PTG were not explored ( 14 ).…”
Section: Introductionmentioning
confidence: 99%